PENGARUH FREKUENSI MAKAN TERHADAP JAM KERJA PENEBANG JATI DI KPH JOMBANG - Maman Mansyur Idris; Sona Suhartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
One of heavy work in the forestry activity in Indonesia is manual tree felling of the teak. This work needs much physical labor. Grandjean (1982) states that an extreem physical exertion needs energy about 4,500 kcal/day.In order to continue teak production it is needed to improve welfare of the laborer by giving a better nutrition.A study was conducted to evaluate the effect of calorie intake on the performance of the laborer and data were analyzed by using tabulation. The result showed that eating frequency are highly significant for teak tree fellers productive working hour, age group of 18-40 years with their average productive working hours were 5 hours, 9 minutes and 29 seconds for two times eating frequencies. Further the average of 6 hours, 21 minutes and 41 seconds for three times eating frequencies, and for age group 40 years up were 4 hours, 37 minutes and 25 seconds for two times eating frequencies and 5 hours, 10 minutes and 36 seconds for three times eating frequencies